An l-proline based thermoresponsive and pH-switchable nanogel as a drug delivery vehicle. Issue 17 (9th April 2018) - Salinas, Y.; Castilla, A. M.; Resmini, M.
Abstract : The synthesis and characterisation of a novel dual stimuli-responsive nanogel, based on thermoresponsive N-n -propylacrylamide and anl -proline based monomer acting as a pH-switcher, is reported here. Abstract : The synthesis and characterisation of a novel dual stimuli-responsive nanogel, based on thermoresponsive N-n -propylacrylamide and anl -proline based monomer acting as a pH-switcher, is reported here. The effect of the crosslinker/co-monomer ratios was studied to demonstrate the relationship between the chemical structure, degree of hydrophobicity and physico-chemical characteristics of the nanogels. Tailoring of the thermoresponsive properties was achieved by altering crosslinker N, N ′-methylenebis(acrylamide) content between 10 and 50 mol%, in combination with three thermoresponsive monomers N-n -isopropylacrylamide, N-n -propylacrylamide and N -acryloylpyrrolidine. A library of 25 different combinations of monomers and crosslinkers was obtained and characterised by dynamic light scattering and UV-Vis spectroscopy. The nanogel based on N-n -propylacrylamide and 10 mol% crosslinker was then co-polymerised with anl -proline based monomer to introduce a pH-switch. This nanogel was obtained with <10 nm particle size and a VPTT ca. 43 °C, and was used to demonstrate a drug delivery capability using Nile Blue A as a model drug. Detailed studies demonstrated maximum drug release at lower pH and 43 °C, thus confirming the dual stimuli switch.